Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Given $A$ and $B$ are complex numbers.

I want to request anyone who might know any formulas for expanding this following expression. $$ |A-B|^{2n}$$ where $n$ is an integer.

The one that I commonly used for an order of $2$, i.e. $n=1$ is $$ |A-B|^{2}= (A-B)(A-B)^*$$ where the $[.]^*$ means the Hermitian adjoint.

So I want to see if I can increase the order from $n=1$ to $n=\{2,3,4,5...\}$ Is there such rule? Maybe like a Pascal triangle theorem and/or Binomial property?

Thanks in advance!

share|cite|improve this question
Specifically for $2n$, you can use what you already stated above: $|A - B|^{2n} = (|A - B|^2)^n = ((A - B)(A - B)^*)^n = (A - B)^n(A - B)^{* n}$. If you have $2n + 1$, then this obviously becomes $|A - B|(A - B)^n(A - B)^{*n}$. – William Mar 29 '12 at 9:07
up vote 3 down vote accepted

$$ \begin{eqnarray} \left|A-B\right|^{2n} &=& \left|(A-B)^n\right|^2 \\ &=& \left|\sum_{k=0}^n\binom nkA^k(-B)^{n-k}\right|^2 \\ &=& \left(\sum_{k=0}^n\binom nkA^k(-B)^{n-k}\right)\left(\sum_{k=0}^n\binom nkA^{*k}(-B^*)^{n-k}\right)\;. \end{eqnarray} $$

share|cite|improve this answer

What about $|A-B|^{2n}=(|A-B|^2)^n=\left((A-B)(A-B)^* \right)^n$?

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.